Genetic Evaluation of Reproductive and Productive Traits in Zaraibi Goats Under Tropical Climatic Conditions - Aya Esam Hemada; Heba Abd El-Halim Ahmed; Asmaa Zayed Mohamed; Adel Salah Khattab; Oludayo Michael Akinsola; Thiruvenkadan Aranganoor Kannan (Ruminants, 2025)
Understanding the genetic and phenotypic basis of economically important traits is essential for designing effective breeding programs in livestock. This study aimed to evaluate the phenotypic performance and estimate genetic parameters for one reproductive trait—litter size at birth (LSB)—and three pre-weaning growth traits—birth weight (BW), weaning weight (WW), and average daily gain (ADG)—in a population of 1888 Zaraibi kids born between 2018 and 2023. Genetic parameters were estimated using animal models implemented in the MTDFREML software. The overall least squares means (±standard error) for LSB, BW, WW, and ADG were 2.22 ± 0.02, 2.03 ± 0.01 kg, 10.22 ± 0.05 kg, and 90.00 ± 0.50 g/day, respectively. Statistical analyses indicated that month of birth, year of birth, and type of birth had significant (p < 0.05) effects on all traits, while the sex of the kids had no significant effect (p > 0.05) on LSB. Direct heritability estimates (h2d) derived from Model 1 (including additive genetic, permanent environmental, and residual effects) were 0.13 ± 0.01 for LSB, 0.30 ± 0.04 for BW, 0.38 ± 0.01 for WW, and 0.30 ± 0.10 for ADG. Under Model 2 (which incorporated maternal genetic effects and their covariance with direct genetic effects), maternal heritability (h2m) estimates for LSB, BW, WW, and ADG were 0.05 ± 0.01, 0.15 ± 0.01, 0.12 ± 0.01, and 0.14 ± 0.01, respectively. Overall, the results emphasize the importance of maternal genetic effects in influencing pre-weaning growth traits. Therefore, maternal genetic components should be explicitly considered in genetic evaluation and selection strategies aimed at improving early growth performance in Zaraibi goats.